Risk factors associated with uncontrolled blood pressure among patients with non-dialysis chronic kidney disease in Vietnam - Nguyen, Van Thi Hai; Sriyuktasuth, Aurawamon; Phligbua, Warunee (Belitung Raya Foundation, Indonesia, 2021)
Background: Uncontrolled blood pressure rates are high in patients with non-dialysis chronic kidney disease, worsening the disease progression and leading to end-stage renal disease. However, studies on uncontrolled blood pressure in patients with non-dialysis chronic kidney disease and its associated factors in Vietnam are scarce. Objectives: This study aimed at identifying uncontrolled blood pressure rates and risk factors associated with uncontrolled blood pressure among Vietnamese patients with non-dialysis chronic kidney disease. Methods: A cross-sectional, correlational study design was employed among 182 participants coming to follow up at two tertiary hospitals in Vietnam. The participants were selected by a convenience sampling technique. Data were collected using Participant Demographic Information Form, Clinical Characteristics Form, Alcohol Use Disorders Identification Test, Pittsburgh Sleep Quality Index, Charlson Comorbidity Index, and an automated office oscillometric upper arm device. Descriptive statistics, Chi-square, Fisher’s Exact Test, and binary logistic regression were used to analyze the data. Results: 63.2% of the participants could not control their BP less than 130/80 mmHg. Poor sleep quality (OR 2.076, 95%CI 1.059-4.073, p=.034) and severe comorbidities (OR 2.926, 95%CI 1.248-6.858, p=.013) were risk factors associated with uncontrolled blood pressure among Vietnamese patients with non-dialysis chronic kidney disease. Interestingly, the study found a high rate of awareness toward the importance of blood pressure control but a low rate of known blood pressure targets. Conclusion: Uncontrolled blood pressure rates among Vietnamese patients with non-dialysis chronic kidney disease were high. Sleep quality and comorbidity severity were significantly associated with uncontrolled blood pressure in this population. To achieve blood pressure targets, nurses and other healthcare providers should pay more attention to the patients with poor sleep quality and severe comorbidities.